2023
DOI: 10.3390/jcm12124007
|View full text |Cite
|
Sign up to set email alerts
|

Under the Hood: Understanding the Features of Mucin in Pseudomyxoma Peritonei

Abstract: Pseudomyxoma peritonei (PMP) is a rare malignant growth characterized by the production of mucin and the potential for peritoneal relapse. This study aimed to investigate the immunohistochemical and biological characteristics of mucin in patients with cellular and acellular PMP. We prospectively analyzed mucin specimens obtained from our patient cohort and described the composition and type of mucin present in each sample. A metagenomic analysis of the samples was performed to investigate the bacterial composi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…However, the interaction relationship and mechanism between these bacteria and MUC2 have not been reported. Villarejo-Campos et al [86] performed 16S sequencing on PMP mucinous tumor tissue, and the results suggested that Proteobacteria was the dominant phylum and Pseudomonas was the dominant genus. Previous studies have shown that Pseudomonas is directly related to the overexpression of mucins [87].…”
Section: Intestinal Floramentioning
confidence: 99%
See 1 more Smart Citation
“…However, the interaction relationship and mechanism between these bacteria and MUC2 have not been reported. Villarejo-Campos et al [86] performed 16S sequencing on PMP mucinous tumor tissue, and the results suggested that Proteobacteria was the dominant phylum and Pseudomonas was the dominant genus. Previous studies have shown that Pseudomonas is directly related to the overexpression of mucins [87].…”
Section: Intestinal Floramentioning
confidence: 99%
“…or whether it was the colonization of Pseudomonas [86] or other reasons, the mechanism of this kind of tumor cell-independent mucin production merits further discussion.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…It is associated with malignant tumors in the appendix (see Figures 4 and 5); however, there is a debate ove the specific epithelium from which it arises. The hypothesis that ovaries might be an al ternative main location of PMP genesis is regarded as plausible, but lacks a complete ex planation in terms of immunochemistry [3] (see Figures 6 and 7). In a study designed by Yan [4], the tumors exhibited positivity for CK20, CDX2, CEA, and Villin.…”
Section: Introductionmentioning
confidence: 99%